Solid‐State Electrolytes: Revealing the Short‐Circuiting Mechanism of Garnet‐Based Solid‐State Electrolyte (Adv. Energy Mater. 21/2019). Issue 21 (4th June 2019) - Song, Yongli; Yang, Luyi; Zhao, Wenguang; Wang, Zijian; Zhao, Yan; Wang, Ziqi; Zhao, Qinghe; Liu, Hao; Pan, Feng
Abstract : In article number1900671, Feng Pan and co‐workers investigate the short‐circuiting mechanism of garnet Li7 La2.75 Ca0.25 Zr1.75 Nb0.25 O12 (LLCZN). Instead of propagating uniaxially from one electrode to the other in a dendritic form, metallic lithium is formed within the solid electrolyte. It is found that the grain boundaries of LLCZN provide electron pathways, which allow Li + to be reduced by electrons into metallic Li.